Presence of quorum sensing system, virulence genes, biofilm formation and relationship among them and class 1 integron in carbapenem-resistant clinical Pseudomonas aeruginosa isolates - Başkan, Ceren; Sırıken, Belgin; Tüfekci, Enis Fuat; Kılınç, Çetin; Ertürk, Ömer; Erol, İrfan (Springer Science and Business Media LLC, 2022)
Carbapenems are the most effective agents for treating clinical P. aeruginosa (PsA) infections. During an infection, a quorum-sensing (QS) system and its regulating virulence genes have a great role. The aim of the study was to detect the presence of a las and rhl QS system and related virulence genes, biofilm formation and a class 1 (Cls1) integron. A total of 52 carbapenem-resistant PsA (CRPsA) isolates obtained from Kastamonu, Turkey was analyzed. For the isolation and identification of CRPsA isolates, a conventional culture method, an automated VITEK-2 compact system, and oprL gene-based molecular technique were applied. The two QS system genes were detected in 51 (98.1%), and co-existed of four two QS system genes (lasI/R and rhIl/R genes) were determined in 41 (78.8%) of the isolates. algD, lasB, toxA and aprA genes were detected in between 46.1 and 88.5%, and co-existence of four two QS system genes with four virulence genes were detected in 40.4% of the isolates. Biofilm formation using microtiter plate assay and slime production using Congo Red Agar and Cls1 integron were determined in 84.6%, 67.3% and 51.9% of the isolates, respectively. According to statistical analyses results, there was a significant positive correlation (p < .10) between the las and the rhl systems and a strongly and positive correlation (p < .01 or p < .05) between the rhl system-three virulence genes and slime production-and among some virulence genes. In conclusion, the CRPsA isolates tested in the study are highly virulent and QS systems have a significant role in pathogenesis.
Keywords: Bacterial Proteins; Carbapenems; Virulence; Virulence Factors; Biofilms; Drug Resistance, Bacterial; Pseudomonas aeruginosa; Quorum Sensing; Integrons; 3. Good health